2016
DOI: 10.1071/am14039
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and characteristics of the platypus (Ornithorhynchus anatinus) in the Murrumbidgee catchment

Abstract: Little is known of the current status of platypus (Ornithorhynchus anatinus) populations in the Murrumbidgee catchment and other west-flowing rivers in the Murray–Darling Basin. Platypus distribution in the Murrumbidgee catchment was determined from sightings, reports by government departments, the literature and a capture–release study. The platypus was found to be widespread in the catchment, including all subcatchment and elevation categories, but most reports were from the middle and upper subcatchments. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 15 publications
2
7
0
Order By: Relevance
“…We found no evidence of mucormycosis in the study animals but found a new differential diagnosis for this disease. Platypuses are sexually dimorphic in body length and body mass and are generally larger in Tasmania (Grant and Temple-Smith 1983;Connolly and Obendorf 1998;Munks et al 1998;Bethge 2002;Koch et al 2006;Gust and Griffiths 2011). Our findings are consistent with these observations.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…We found no evidence of mucormycosis in the study animals but found a new differential diagnosis for this disease. Platypuses are sexually dimorphic in body length and body mass and are generally larger in Tasmania (Grant and Temple-Smith 1983;Connolly and Obendorf 1998;Munks et al 1998;Bethge 2002;Koch et al 2006;Gust and Griffiths 2011). Our findings are consistent with these observations.…”
Section: Discussionsupporting
confidence: 83%
“…Our findings are consistent with these observations. Studies of Tasmanian platypuses have shown mean mass in different river systems in the ranges 0.91-1.65 kg and 1.47-2.5 kg for females and males, respectively (Connolly and Obendorf 1998;Stewart 2001;Bethge 2002;Koch et al 2006;Gust and Griffiths 2011). Mean body masses in our study were near the middle of these ranges and were very close to the mean values of 1.3 kg for females and 2.1 kg for males reported by Macgregor (2008) in the Inglis River Catchment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations